Non-material matters: A call for integrated assessment of benefits from ecosystems in research and policy. (January 2019) - Adams, Alison; Morse, Joshua
Highlights: Policy uptake of non-material benefits from nature lags behind theory. Over-emphasis on material benefits leaves environmental policy vulnerable to bias. Systematic analysis of non-material benefits could strengthen environmental policy. Both policy and academic institutions must encourage this paradigm shift. Abstract: Systematic assessment of non-material benefits from healthy ecosystems is a critical complement to economic valuations in policy. Several frameworks of increasing nuance and complexity have been proposed to facilitate collection of data on non-material benefits from healthy ecosystems, as well as transmission of these data to policymakers. However, systematic incorporation of such data in policy arenas lags behind the theory. We argue that failure to incorporate data on non-material benefits, and thus failure to account for the full range of values at stake for impacted parties, leaves natural resource policy processes especially vulnerable to partisan influences. We examine a recently published account of conflicting economic benefit-cost analyses and their policy contexts to illustrate opportunities for robust analysis of non-material benefits to strengthen the policy process. Building on this analysis, we call for practical applications, complementing recent theoretical advances, to more comprehensively research the full range of benefits from ecosystems and incorporate such research into policy decisions. Doing so would enhance both the scientific and democratic merit of natural resource policy efforts.